Cognitive impairment assessed by static and dynamic changes of spontaneous brain activity during end stage renal disease patients on early hemodialysis - Wu, Yunfan; Li, Rujin; Jiang, Guihua; Yang, Ning; Liu, Mengchen; Chen, Yanying; Chen, Zichao; Yu, Kanghui; Yin, Yi; Xu, Shoujun; Xia, Bin; Meng, Shandong (Frontiers in Neurology, 2025)
BackgroundCompared with the general population, patients with end-stage renal disease (ESRD) undergoing maintenance hemodialysis (ESHD) exhibit a higher incidence of cognitive impairment. Early identification of cognitive impairment in these patients is crucial for reducing disability and mortality rates. Examining the characteristics of static and dynamic regional spontaneous activities in ESHD cases may provide insights into neuropathological damage in these patients.MethodsResting-state functional magnetic resonance images were acquired from 40 patients with early ESHD (3 or 4 times/week for more than 30 days but less than 12 months) and 31 healthy matched controls. Group differences in regional static and dynamic regional homogeneity (ReHo) were identified, and correlations examined with clinical variables, including neuropsychological scale scores, while controlling for covariates. Receiving operating characteristic (ROC) curve analyses were conducted to assess the accuracy of ReHo abnormalities for predicting cognitive decline among early ESHD.ResultsThe ESHD group exhibited significantly reduced static and dynamic ReHo in the temporal and parietal lobes, including regions involved in basal ganglia–thalamus-cortex circuits, the default mode network, and ventral attentional network. Several static and dynamic ReHo abnormalities (including those in the right parietal and left middle temporal gyrus) were significantly correlated with neurocognitive scale scores. In addition, the dynamic ReHo value of the left superior temporal gyrus was positively correlated with depression scale scores. Comparing the ROC curve area revealed that numerous brain regions with altered ReHo can effectively distinguish between patients with ESHD and those without cognitive impairment.ConclusionOur study found that spontaneous activity alterations located in the basal ganglia-thalamus-cortex circuit, default mode network, and ventral attentional network are associated with the severity of cognitive deficits and negative emotion in early ESHD patients. These findings provide further insight into the relationship between cognitive impairment and underlying neuropathophysiological mechanisms underlying the interplay between the kidneys and the nervous system in ESRD patients, and provide further possibilities for developing effective clinical intervention measures.